Static liquefaction of very loose sand-slag-bentonite mixtures - Sabbar, A.; Chegenizadeh, Amin; Nikraz, Hamid (Japanese Geotechnical Society, 2016)
Static liquefaction is a highly destructive mechanism in the failure of soil deposits caused by a sudden loss of effective stress accompanied by vast deformations and a rapid build-up of pore water pressure that can cause soils to behave like liquids. This study examined liquefaction phenomena in saturated clean Perth sand, sand containing 3% bentonite, sand containing slag (2%, 4%, and 6%), and sand containing both 3% bentonite and slag (2%, 4%, and 6%). Undrained static triaxial compression tests were implemented on very loose mixtures at three initial confining pressures (100, 150, and 200. kPa). Static liquefaction (zero deviatoric stress and zero effective confining pressure) was observed at the lowest relative density and the lowest confining pressure. The liquefaction potential of the clean sand and the sand mixtures decreased with increases in confining pressure and relative density. The slag reduced the liquefaction susceptibility by reducing the inter-particle voids and producing a stable fabric. The optimum slag content was found to be 4%. Mixing clean sand with 3% bentonite produced a vulnerable fabric which exhibited high compressibility and a high level of excess pore water pressure. All sand-slag-bentonite mixtures showed non-flow behaviour and low excess pore water pressure. The mixture of sand with 4% slag and 3% bentonite exhibited the highest effective stress and the lowest excess pore pressure. It was revealed that the normalisation between the maximum and the minimum deviatoric stresses, namely, the brittleness index, can be used to quantify the liquefaction potential of clean sand and sand-slag-bentonite mixtures.